Effect of Low-Temperature Preheating on the Physicochemical Properties and Energy Quality of Pine Sawdust - Tingzhou Lei; Yang Mei; Yuanna Li; Yunbo Wang; Suyang Liu; Yantao Yang (Energies)
The advantages of torrefaction preheating, including the production of a hydrophobic solid product, improved particle size distribution, enhanced fuel properties with fewer environmental issues, decreased moisture content, and reduced volatile content. In order to meet the technical requirements of biomass oriented value-added and energy saving and emission reduction, pine sawdust (PS) was taken as the research object, and the physicochemical properties of the PS samples preheated at a low temperature were analyzed by synchronous thermal analysis (TG-DSC), Fourier transform infrared spectroscopy (FT-IR), scanning electron microscope (SEM), and organic element analyzer (EA). The effect of preheating at a lower temperature on the physicochemical properties of PS was discussed. The results showed that, under the preheating condition of 200 °C, compared with PS, the water content of PS-200 decreased by 3.23%, the volatile content decreased by 3.69%, the fixed carbon increased by 6.81%, the calorific value increased by 6.90%, the equilibrium water content decreases from 7.06% to 4.46%, and the hydrophobicity increases. This research, based on the improvement of the quality of agricultural and forestry waste and the promotion of the strategy of converting waste into energy, has contributed to the advancement of sustainable energy production.